Children with progressive and relapsed pleuropulmonary blastoma: A European collaborative analysis. Issue 12 (5th September 2021) - Sparber‐Sauer, Monika; Tagarelli, Arianna; Seitz, Guido; Sorg, Benjamin; Bien, Ewa; Bel‐Ami, Tal; Pourtsidis, Apostolos; Lopez Almaraz, Ricardo; Koscielniak, Ewa; Ferrari, Andrea; Orbach, Daniel; Bisogno, Gianni; et al.
Abstract: Background: Children with progressive (PD) or relapsed disease (RD) of pleuropulmonary blastoma (PPB) type II/III are known to have a very poor outcome. Methods: A retrospective review of children registered in national and European databases and trials (2000–2018) with diagnosis of PPB type II/III and PD or RD was performed. Results: A total of 35 patients with PPB were analysed: patients with PD ( n  = 9) and RD ( n  = 26). Patients experienced PD at the median age of 3.9 years [range, 0.5–17.8] despite surgery, chemotherapy (CHT, n  = 9) and radiotherapy (RT, n  = 1) with a median time to progression of 0.58 years [range, 0.02–1.27] from diagnosis. All of them died. Patients suffered from RD at the median age of 4.3 years [1.7–15.1], median delay to relapse 1.03 years [range, 0.03–2.95]. RD occurred locally ( n  = 12), combined ( n  = 1) and in metastatic sites ( n  = 13): central nervous system ( n  = 11) and unspecified site ( n  = 2). Patients were treated with salvage CHT ( n  = 20), surgery ( n  = 10) ± RT ( n  = 10). After a median follow‐up of 4.2 years [range, 2.1–14.6], a second complete remission (CR) was achieved in nine out of 26 patients. Patients were alive in the second CR ( n  = 6), in the third CR ( n  = 1), in partial remission ( n  = 2) and lost of follow‐up ( n  = 1). Five‐year event‐free survival (EFS) and overall survival (OS) for patients with RD were both 37% (±19, CI 95%). Local therapy (surgery, RT) had a favourable impact on OS ( p  = 0.03 and 0.02, respectively). Conclusions: Cure of patients with RD of PPB type II/III with multimodal treatment is possible but rare. Progressive PPB is fatal and patients need new treatment options.